2018
DOI: 10.1002/acm2.12274
|View full text |Cite
|
Sign up to set email alerts
|

Geometric accuracy of the MR imaging techniques in the presence of motion

Abstract: Magnetic Resonance Imaging (MRI) is increasingly being used for improving tumor delineation and tumor tracking in the presence of respiratory motion. The purpose of this work is to design and build an MR compatible motion platform and to use it for evaluating the geometric accuracy of MR imaging techniques during respiratory motion. The motion platform presented in this work is composed of a mobile base made up of a flat plate and four wheels. The mobile base is attached from one end and through a rigid rod to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The MR geometric distortion as well as blurring artifacts during motion presented in this study were measured and reported in our earlier study [36]. In that study, Axial, sagittal and coronal Cine MR slices acquisitions of an in-house motion phantom were compared with the CT images using our in-house developed software.…”
Section: Mr Geometric Accuracy Measurementmentioning
confidence: 93%
See 1 more Smart Citation
“…The MR geometric distortion as well as blurring artifacts during motion presented in this study were measured and reported in our earlier study [36]. In that study, Axial, sagittal and coronal Cine MR slices acquisitions of an in-house motion phantom were compared with the CT images using our in-house developed software.…”
Section: Mr Geometric Accuracy Measurementmentioning
confidence: 93%
“…In this current work, we present a methodology for the development of digital phantoms used in order to investigate the dosimetric impact of MR system-related inaccuracy during motion on treatment plans in an MR-only workflow. MR distortion maps as well as blurring artifacts calculated in our previous work [36] were used to deform different type of digital phantoms. Dose plans were initially generated and optimized on the distorted datasets and then transferred to the original datasets to calculate new dose distributions and to study the MR geometric inaccuracy impact on dose-volume histograms (DVHs).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also important to note that MRI suffers from geometrical distortion which could affect MRI-based dose calculation and organ motion quantification. This aspect was reviewed in Schmidt and Payne (2015) and, to our knowledge, just one publication has been reported dealing with moving organs (Torfeh et al 2018). Effects of geometrical distortion are outside the scope of this review but require additional evaluation on the accuracy of MRI for treatment guidance and protocols should be defined to account for these uncertainties.…”
Section: Future Challengesmentioning
confidence: 99%